Peningkatan Soft-skills Melalui Pelatihan English for Jobseekers Bagi Lulusan Program Beasiswa - Sri Lestari (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
This community service is aimed at improving the soft skills of the Digital Talent Scholarship program graduates. They were graduated from the scholarship program and are looking for jobs including fresh graduates from universities and high schools, final-years university students, government employees, and job seekers in Indonesia. They completed the digital training programs and were allowed to take additional soft-skills training. One of the training is English for Jobseekers. The virtual training was held in two batches, August and October 2021 for full five days each batch. This training is to help the participants to use correct English for job hunting purposes namely writing an impressive CV, composing a cover letter, and answering job interview in English. Through presentation, discussion, simulation, and role play, the training pushed the participants to engage actively in each session. As a result, the participants have a well-written CV and cover letter and can respond the interview questions in English effectively. The community service program has successfully improved the participants’ English skills for job seeking. Therefore, it is recommended to conduct similar trainings for other groups of jobseekers.